Opportunities for Reference Services: The Bright Side of Reference Services in the 1990's, 1st edition - Katz, Bill (Routledge, 2020)
This book, first published in 1991, explores the changing roles of reference services and offers advice and practical ideas to guide librarians through the increasingly tangled maze of duties being thrust upon the reference staff. Although the everyday work of the reference librarian is often taken for granted, these insightful chapters illuminate the essential service performed by the reference librarians as they facilitate access to information for a wide variety of users. Furthermore, this book helps reference librarians face the future by examining the technological and service developments that will challenge their profession.